Adverse Events Following Immunization (AEFI) with CoronaVac COVID-19 Vaccine among Clinical Clerkship Students at the Faculty of Medicine, Syarif Hidayatullah State Islamic University, Jakarta, Indonesia (Bangladesh Journal of Medical Science, 2023)
Objective: Clinical clerkship students, as adolescent health workers, have been first recipients of the COVID-19 vaccination programme. The success rate and trust of recipients in the program have been impacted by adverse events following immunization (AEFI). This study aims to determine the AEFI of the CoronaVac vaccine among clinical clerkship students at the Faculty of Medicine, State Islamic University, Jakarta.Material and Methods: This study used cross sectional methods with a total of 225 subjects completing a questionnaire. The CoronaVac vaccine was administered twice with 2 week interval. AEFI was evaluated after 30 minutes, 24 hours, and on the third day.Results and discussion: 73.3% of the participants were female, 20-25 years old. AEFIs were found in 57.8 % of all participants in the first and second doses vaccination. The most common local AEFI was pain at the site injection, accounting 27.1 % which occurred 30 minutes after second dose vaccination. The most common systemic AEFI was drowsiness, accounting for 18 % which occurred 24 hours after first dose vaccination. Other systemic AEFIs were headache, fatigue, and chills. There was significant association between AEFIs and females but no significant association with history of allergy, comorbidities, and history of previous COVID-19 . AEFIs were mild, no special treatment or hospitalization were required.Conclusion: The AEFIs of the CoronaVac vaccine among students were mild and had significant association with females. The study is expected to increase the public’s confidence in the COVID-19 vaccination program and to create awareness of its safety.Bangladesh Journal of Medical Science Vol. 22 No. 03 July’23 Page :545-552